An Error Analysis of Students’ Translation In Narrative Text - Jannah, Icha Rauzatul; Yenni , Cut; Rahmi , Taufikur; Alimnur , Alimnur (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2022)
This research was conducted based on the fact that most students still made many errors in coveying the meaning from Indonesian to English language. Lack of vocabularies, facing an ambiguity from Indonesian to English, word, phrase, and sentence. Therefore, the purposes of this research are (1) to find out types of errors made by students in translating narrative text and (2) to find out the causes of errors made by the students. The design applied in this research was qualitative in type of case study. Meanwhile, the techniques of data collection were documentation and interview. Nine students were considered purposively as subject categorized into high, middle, and low levels. The technique of analyzing data of this research consisted of data condensation, data display, and conclusion/ verification which was found in Miles and Huberman, and Saldana’s model. The result of this research found that (1) there were four types of errors made by the eleventh grade students, namely: omission, additions in simple addition, misformation in regularization and alternating form, and the last one missordering. The highest percentage was misformation. The second was omission. The third was missordering, and the lowest percentage was additions. It is also found that (2) those errors occured because of carelessness, first language interference, and translation. However, it is expected that the students may learn Indonesian and English seriously in order to increase their awareness in both languages. It is also important that the English teachers provide some creative strategy in learning to avoid any boredom in teaching process.